Effects of Environment and Input Technology on Human Working memory for Medical Charting Information. (September 2014) - Spangler, Angela; Hedge, Alan
This study investigated the role of the location updating effect (the memory deficit associated with passing through a doorway) and input technology (paper, a tablet PC or a laptop) on working memory for medical charting information, because in many hospitals physicians and nurses often leave the patient bedside to enter their medical information elsewhere. 48 participants watched medical scenario videos (note taking was allowed) and recalled patient information onto a medical chart presented either as a paper chart or electronically on a tablet, and a laptop, presented in randomized order. Post-video, each P either entered a new room through opening 3 doorways, walked back and forth in the original room for the same duration, or simply waited while seated for the same duration. The items to be recalled included demographic information, narrative information related to medical history, numeric data in the form of vital signs and medication data in a checkbox format. Results show that significantly more items were recalled to paper (13.5) compared to either the laptop (11.8) or tablet (9.7). There was no evidence of a location updating effect.